Hubungan Disiplin Kerja dan Motivasi Kerja dengan Efektivitas Kerja Pegawai PT. Aqua Golden Mississipi Cicurug Sukabumi - Dedi Kustiawan (LPPM AMIK Citra Buana Indonesia, 2017)
Aqua Golden Mississippi Cicurug Sukabumi is one of the company engaged in the provision of bottled water in Indonesia, which lead employees to work productively and can carry out their duties properly. Problem often encountered leader PT. Aqua Golden Mississippi is how to find the best way to be taken in order to mobilize and increase the effectiveness of employees in order to consciously and responsibly carry out the task as well as possible, because every employee has a need and desire different that leaders must know and understand the needs and wishes of the members. Based on the background of the problem, then that becomes the central issue in this study is how much influence the work of discipline and motivation to work against the effectiveness of employees, from the data above the authors try to identify the problem as follows: How does the discipline of work, how to discipline the working relationship with the effectiveness of employees, how the work motivation of employees, how the relationship with the effectiveness of work motivation, how the effectiveness of employees, and how relationships work discipline and motivation of employees working with the effectiveness of employees in PT. Aqua Golden Mississippi Cicurug Sukabumi Research used in this research is descriptive method. Method is a descriptive study to determine the value of independent variables. In this study the descriptive method used to see an overview of each independent variable. While the unit is the unit of analysis that will be used to explain or describe the characteristics of a larger set of objects again. The results of assessment of the relationship of work discipline and motivation to work with employee work effectiveness can be summarized as follows: 1) Employee labor relations discipline (X1) with employee work effectiveness (Y) is shown by a correlation value of r X 1 with Y = 0.816, means a relationship (X1) and (Y) very strong, and its influence + (positive). 2) Labor relations employee motivation (X2) with employee work effectiveness (Y) is shown by the value of X2 with Y correlation of r = 0.890, means a relationship (X2) and (Y) very strong, and its influence + (positive). 3) Relationship of labor discipline (X1) and employee motivation (X2) together with employee work effectiveness (Y) is shown by the multiple correlation, which shows the value of r = 0.949, and the magnitude of the relationship of labor discipline and the effectiveness of employee work motivation employees working at 90.1% (R square = 0.901), this statement has meaning relations (X1) and (X2) and (Y) has a very strong positive relationship. Keywords: Employment Relations, Work Motivation Discipline, Employee Work Effectiveness